Biomechanical analysis of running foot strike in shoes of different mass - Wang, I.-L.; Graham, R. B.; Bourdon, E. J. P.; Chen, Y.-M.; Gu, C.-Y.; Wang, L.-I. (Journal of Sports Science & Medicine, 2020)
Different shoes and strike patterns produce different biomechanical characteristics that can affect injury risk. Running shoes are mainly designed as lightweight, minimal, or traditional cushioned types. Previous research on different shoes utilized shoes of not only different mass but also different shoe structures. However, it is unclear whether biomechanical changes during running in different shoe types with differing mass are the result of the structural design or the mass of the shoe. Thus, the purpose of this study was to investigate the effect of shoes of different mass on running gait biomechanics. Twenty male runners participated in this study. The experimental shoe masses used in this study were 175, 255, 335 and 415 g. The peak vertical ground reaction force increased with shoe mass (p < 0.05), but the strike index, ankle plantarflexion at initial contact, peak moment of the ankle during the stance phase, and initial contact angles of the lower extremity joints did not change. During the pre-activation phase, the integrated EMG data showed that the tibialis anterior muscle was the most activated with the 175 g and 415 g shoes (p < 0.05). During the push-off phase, the semitendinosus, lateral gastrocnemius and soleus muscles displayed higher activation with the heavier shoes (p < 0.05). The center of pressure also moves forward; resulting in mid foot striking. The lightest shoes might increase gastrocnemius muscle fatigue during the braking phase. The heaviest shoes could cause semitendinosus and triceps surae muscle fatigue during the push-off phase. Therefore, runners should consider their lower extremity joints, muscle adaptation and cushioning to remain in their preferred movement path. Key Points